Morphology of first seven larval stages of the striped soldier shrimp, Plesionika edwardsii (Brandt, 1851) (Crustacea: Decapoda: Pandalidae) from laboratory reared material - Landeira, José María; Lozano-Soldevilla, Fernando; González-Gordillo, Juan Ignacio (Zootaxa, 2009)
With the idea of starting a research program for the biological study of Plesionika edwardsii, eight ovigerous females were collected with artisanal bottom traps at 220 m depth in the Southwest of Gran Canaria island, north-western Africa (27º43.864´N 15º47.822´W), for laboratory larval cultures. The first seven zoeal stages of Plesionika edwardsii were obtained for 20 days after hatching at 23.4 ± 0.4ºC, 10ºC above adult habitat temperature. The zoeal stages are described and illustrated, constituting the first detailed larval description of the genus Plesionika. The larval morphology is compared with previous larval descriptions attributed to Plesionika spp. collected in plankton tows and with descriptions of the first stage of development of Plesionika acanthonotus reared in laboratory.